On the Systemic Features of Urban Systems. A Look at Material Flows and Cultural Dimensions to Address Post-Growth Resilience and Sustainability - Cristiano, Silvio; Zucaro, Amalia; Liu, Gengyuan; Ulgiati, Sergo; Gonella, Francesco (Frontiers in Sustainable Cities, 2020)
NA